الاشراف التربوي ودوره في تسيير وإنجاح العملية التعليمية التعلمية - مقداد, إيمان (جامعة الوادي - University of Eloued, 2022)
مما لاشك فيه أنّ للتربية دورا هاما على مستوى جميع عناصر العملية التعليمية التعلمية في عالمنا سواءً كانت إصلاحا أو مواكبة للتطور الحاصل في مختلف الميادين، فهي تعمل على تحقيق التنمية في ظل الانفجار المعرفي والثورة المعلوماتية لأطرها المتنوعة بما فيها العملية الإشرافية التي هي بمثابة العمود الذي ترتكز عليه، لذا عمدت على إعطاء أهمية للإشراف التربوي باعتباره ركن أساسي من الأركان الرئيسة والفاعلة في أي نظام تعليمي فهو يعمل على تشخيص واقع العملية التعليمية من حيث المدخلات والمخرجات وتحسينها وتطويرها بما يتناسب وتلبية متطلبات المجتمع، ومن جهة إثراء وتطوير المناهج التربوية والمواد التعليمية . وعلى هذا الأساس كان عنوان مقالنا : الإشراف التربوي ودوره في إنجاح العملية التعليمية التعلمية، التي لا بد من تطويرها عن طريق تنمية كفايات المعلم وتزويده بالخبرات التربوية اللازمة وهذا ما سنحاول التركيز عليه في ورقتنا البحثية. Abstract: There is no doubt that education plays an important role at the level of all components of educational learning in our world, whether reform or keeping pace with the development in various fields. It works to achieve development in the light of the knowledge explosion and the information revolution of its various frameworks, including the supervisory process, Therefore, it has given importance to the supervision of education as a cornerstone of the main and effective elements in any educational system, it works to diagnose the reality of the educational process in terms of inputs and outputs and improve and develop in proportion to meet the requirements of the community, on the one hand And development of educational curricula and educational materials. On this basis was the title of our intervention: educational supervision and its role in the success of educational learning process, which must be developed by developing the teacher's qualifications and provide him with the necessary educational expertise and this is what we will try to focus on in our research paper.
مقال
Keywords: الإشراف التربوي،الدور،الأهمية،العملية التعليمية،الخصائص; educational supervision, role, importance, educational process, characteristics.